A situational analysis of ear and hearing care in South Korea using WHO ear and Hearing Care Situation Analysis tool - Lee, Juhyeong; Yoon, Chul Young; Lee, Junhun; Kong, Tae Hoon; Oh, Seung Ha; Seo, Young Joon (Frontiers in Public Health, 2023)
Objectives The WHO emphasizes lifelong management of hearing diseases such as hearing loss and advocates for prevention. The Ear and Hearing Care Situation Analysis (EHCSA) tool was designed by the WHO for assessment and quality improvement of state-led management of hearing loss prevention and management programs. The purpose of this study was to use the EHCSA to assess the ear and hearing management program in Korea and to establish goals consistent with best practices for improving policies and services related to ear and hearing care. Methods The EHCSA was used as a need assessment of the ear and hearing management services in the country. The EHCSA consists of two sections. Section 1 consists of 41 questions to evaluate health policies and support services. Section 2 consists of 203 questions to evaluate human resources and services of the ear and hearing management sector. Results There are an estimated 800,000 people with hearing loss in Korea. Policies such as hearing aid support are in place, and outreach services such as free hearing tests are also being actively conducted. In all medical institutions, ear and hearing management treatment and medication prescriptions could be received without barriers. Workers in the fields of ear and hearing management, such as audiologists, language therapists, special education teachers, and sign language interpreters, are specialized and have well-established guidelines for training. Conclusion Overall, the domestic ear and hearing management sector has confirmed that policies and services are well-prepared in comparison with advanced countries such as the United States, Iran, and China. The use of the EHCSA was functional in collecting data on the current state of domestic ear and hearing management policies and services in Korea, can be used for continuous quality improvement and expansion of medical services, and can be used as a reporting mechanism to the WHO.